Oscillatory behaviour of magnetic and magneto-optical properties in Fe-Pt thin-film structures - Shalyguina, EE; Shin, KH (ELSEVIER SCIENCE SA, 2001)
Results of investigations into the influence of Pt On the magnetic and magoneto-optical properties of Fe-Pt-Fe. trilayers and the sandwich of wed-e-shaped Fe and Pt layers are presented. The oscillatory behavior of the saturation field, H-S, of the trilayers with changing the Pt-layer thickness, t(pt) was revealed. That was explained by the exchange coupling between the ferromagnetic layers through the nonmagnetic spacer. For the first time, oscillations of the transverse Kerr effect (TKE) with changing Pt-wedge thickness were discovered. The period of these oscillations was found to depend on the Fe-layer thickness and the photon energy of the incident light. TKE spectra of the examined samples were discovered to modify very strongly with increasing t(pt). The peculiarities of the magneto-optical properties of the Fe-Pt thin-film structures were explained by the concept of the spin-polarized quantum well states in the Pt-layer. (C) 2001 Elsevier Science B.V. All rights reserved.
Keywords: EXCHANGE; MULTILAYERS; SYSTEMS; PERIOD; LAYERS; METAL